The book the life story of a technology - Howard, Nicole (Greenwood technographies, 2005)
"This volume provides a broad overview of the printed book's development across many centuries, cultures, and in a variety of fields. It highlights the forerunners and offshoots of books that have come from and been dispersed to all corners of the globe. The creation of a single book requires diverse skills and techniques that have taken centuries to develop. This addition to the Greenwood Technographies series will give readers of all ages a greater appreciation for this familiar phenomenon that is part of everyone's lives." "The volume includes a glossary of terms, a timeline of important events, and a selected bibliography of useful resources for further information."--BOOK JACKET.